2014
DOI: 10.1371/journal.pone.0105411
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Self-Renewing Human Multipotent Marrow Stromal Cells (hMSC) Express Sialyl Lewis X and Actively Adhere to Arterial Endothelium in a Chick Embryo Model System

Abstract: BackgroundThere have been conflicting observations regarding the receptors utilized by human multipotent mesenchymal bone marrow stromal cells (hMSC) to adhere to endothelial cells (EC). To address the discrepancies, we performed experiments with cells prepared with a standardized, low-density protocol preserving a sub-population of small cells that are rapidly self-renewing.MethodsSialyl Lewis X (SLeX) and α4 integrin expression were determined by flow cytometry. Fucosyltransferase expression was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The reliability of the chicken chorioallantoic membrane model has been validated for investigation of the progression and invasiveness of human GCT [32]. It also has been affirmed that rapid self-renewing human multipotent mesenchymal bone marrow stromal cells actively adhere to arterial endothelium in a chicken chorioallantoic membrane model [3,21]. In particular, the chicken chorioallantoic membrane model has been used for evaluating the efficacy of pharmacologic treatment on GCTs by determining the level of angiogenesis [32].…”
Section: Methodsmentioning
confidence: 98%
“…The reliability of the chicken chorioallantoic membrane model has been validated for investigation of the progression and invasiveness of human GCT [32]. It also has been affirmed that rapid self-renewing human multipotent mesenchymal bone marrow stromal cells actively adhere to arterial endothelium in a chicken chorioallantoic membrane model [3,21]. In particular, the chicken chorioallantoic membrane model has been used for evaluating the efficacy of pharmacologic treatment on GCTs by determining the level of angiogenesis [32].…”
Section: Methodsmentioning
confidence: 98%
“…Several research groups showed that application of bone marrow-derived MSCs (BM-MSCs) on the CAM induced neovascularization. 89,[102][103][104] Oskowitz et al demonstrated that this effect was enhanced after serum deprivation of the cells during 30 days. 89 Similarly, MSCs isolated from adipose tissue (AT-MSCs), Wharton's Jelly (WJ-MSCs), placenta (Pl-MSCs), newborn skin (NSSCs), and soft tissues in and around the tooth penetrated the chicken embryo and increased functional blood vessel growth in the CAM 15,22,78,92,93,[105][106][107][108][109][110][111] (Table 1).…”
Section: Stem Cellsmentioning
confidence: 99%
“…108,112 Furthermore, immune-based staining against human antigens is applied to determine the viability and potential incorporation and differentiation of the stem cells into newly formed blood vessels. 92,[110][111][112] Another regularly used method to track transplanted stem cells in the CAM is their prelabeling with fluorescent dyes such as CellTracker Green 104,107,111 or Fluoresbrite carboxylate microspheres. 103 Advanced imaging techniques.…”
Section: Outcome Measures Of Neovascularizationmentioning
confidence: 99%
“…The chick chorioallantoic membrane (CAM) presents a versatile in vivo model for the study of angiogenesis and vascular adaptation [ 30 ] as it facilitates optical access to a developing vascular system in a transparent, two-dimensional layout. Importantly, the CAM allows for extended observation periods for up to 1–2 days, permitting to follow the successive steps of angiogenic development over time [ 31 ]. In the fertilized chicken egg, the CAM is created through fusion of the allantois and the chorion from day 3 of embryonic development and its development continues until embryonic day 13 [ 32 ].…”
Section: Introductionmentioning
confidence: 99%